PENGARUH KEPERCAYAAN, KEAMANAN, PERSEPSI RISIKO, SERTA KESADARAN NASABAH TERHADAP ADOPSI E-BANKING DI BANK BRI SURABAYA - Moh Faqih Afghani; Emma Yulianti (STIE Perbanas Surabaya, 2016)
The purpose of this research was to analyze the effect of each-each variable, trust, security, perceived risk, and awareness to adoption e-banking on bank BRI customers in Surabaya. The process of data collection used convenience sampling method by purpose taking customers that used e-banking BRI in Surabaya. From 90 questionnaires distributed, there were 90 questionnaires returned. The method analysis used the program Spss 16.00. The result showed that three proposed hypothesis was accepted except two hypothesis relationship between security to adoption and perceived risk to adoption had no significant relationship. The management implication and suggestions for the banks as e-banking services providers were also discussed at the end of this research.